Relative age effect and talent identification in youth volleyball players from the Polish volleyball federation sports school - Sliwa, M.; Sadowski, J.; Buszta, M. (Polish Journal of Sport and Tourism, 2021)
Introduction: This study sought to determine differences in the quarterly age distribution of young Polish volleyball players from the Sports School of the Polish Volleyball Federation (SS PVF), to investigate quarterly differences in anthropometric characteristics and jump test results. Material and Methods: RAE of young players from SS PVF (n = 232) born between 1989 and 2002 was identified in the course of the research. Furthermore, the study included anthropometric characteristics and jump test results (attack jump - AJ). Results: The chi-square test (Chi²) revealed the overrepresentation of volleyball players born in quarters 1 and 2, both in the case of graduates (Chi² = 27.32, p < 0.0001) and students who did not finish school (Chi² = 17.95, p < 0.0005). Two-way ANOVA for unbalanced data for the Group factor showed significant differences in the value of estimated marginal means in the case of AJ (F(1,214) = 5.907, p < 0.016) and body mass (BM) (F(1,214) = 5.348, p < 0.022). Conclusions: These results point to the need for better understanding of RAE in order to avoid dropping out or the loss of potential talent, which will contribute to even greater development of volleyball in Poland.